2017
DOI: 10.5935/0004-2749.20170018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of optical coherence tomographic findings between Behcet disease patients with and without ocular involvement and healthy subjects

Abstract: SD-OCT was a useful and non-invasive tool for the detection of retinal nerve degeneration and choroidal changes in patients with Behcet disease even in the absence of ocular involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 0 publications
1
9
0
8
Order By: Relevance
“…Previous studies have assessed ocular neural tissues in patients with BD using OCT and show a reduction in the retinal nerve fiber layer in patients with Neuro-Behçet’s disease and uveitis ( 21 , 46 ). More recently, even patients with BD without ocular disease have shown a significant reduction in the retinal nerve fiber layer, ganglion cell layer, and inner plexiform layer, indicative of sub-clinical retinal nerve degeneration ( 22 ). Our findings are consistent with previous clinical, histopathological and electrophysiological studies reporting peripheral nerve degeneration in BD ( 8 , 9 , 11 , 13 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have assessed ocular neural tissues in patients with BD using OCT and show a reduction in the retinal nerve fiber layer in patients with Neuro-Behçet’s disease and uveitis ( 21 , 46 ). More recently, even patients with BD without ocular disease have shown a significant reduction in the retinal nerve fiber layer, ganglion cell layer, and inner plexiform layer, indicative of sub-clinical retinal nerve degeneration ( 22 ). Our findings are consistent with previous clinical, histopathological and electrophysiological studies reporting peripheral nerve degeneration in BD ( 8 , 9 , 11 , 13 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…In relation to eye involvement in BD, most studies have described an optic neuropathy and retinal pathology with maculopathy and retinal neovascularization ( 19 , 20 ). Studies using optical coherence tomography (OCT) have demonstrated a significant reduction in the thickness of the retinal nerve fiber layer ( 21 ), ganglion cell and inner plexiform layers in patients with BD ( 22 ), while another study showed an initial increase in the nerve fiber layer in those with a short duration of disease, with thinning in those with a longer duration of disease ( 23 ), certainly indicating retinal nerve fiber pathology in patients with BD.…”
Section: Introductionmentioning
confidence: 99%
“…Since the retinal and choroidal microvasculature is particularly susceptible to systemic vascular changes, as observed in diseases such as hypertension and diabetes mellitus, it would be ideal for monitoring disease progression in SSc patients. Additionally, thicknesses of the choroid and retina have been suggested as potential inflammatory biomarkers for autoimmune diseases with a vascular component [7][8][9]. So far, choroidal and retinal abnormalities, such as those reported in SSc patients, have been evaluated by optical coherence tomography (OCT) and fluorescence angiography (FA) [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in its morphology have been suggested to be a useful biomarker of some systemic, 1 neurodegenerative, 2 and ocular diseases. 3 For example, the retinas of individuals with the autoimmune diseases systemic lupus erythematosus and Behcet's disease have been found to be thinner than those of healthy controls, 4,5 even when there was no clinically obvious ocular involvement. 4 Individuals with nonexudative age-related macular degeneration have been observed to have thinner retinas, 6 whereas various forms of macular edema intrinsically result in thickening of the central retina.…”
Section: Introductionmentioning
confidence: 99%